Monitoring rangeland degradation using a novel local NPP scaling based scheme over the "Three-River Headwaters" region, hinterland of the Qinghai-Tibetan Plateau. (15th July 2017) - An, Ru; Wang, Hui-Lin; Feng, Xue-Zhi; Wu, Hong; Wang, Zhe; Wang, Ying; Shen, Xiao-Ji; Lu, Cai-Hong; Quaye-Ballard, Jonathan Arthur; Chen, Yue-Hong; Zhao, Ying-Hui
Abstract: The "Three-River Headwaters" region (TRHR) rangeland ecosystem is extremely sensitive and fragile, and in recent years has undergone continuous degradation. The vast area and severe nature conditions inhibit data acquisition and field experiments, resulting in different understandings about the spatial characteristics and dynamics of rangeland degradation in the region. Therefore, a reliable monitoring method of rangeland degradation is urgently needed for the rangeland protection and management. In this paper, a novel rangeland degradation monitoring scheme based on Local NPP Scaling (LNS) is suggested; A suitable partition program of rangeland productivity unit is set up by using Analytical Hierarchy Process (AHP). The spatio-temporal pattern of degradation in 1990 and 2004 were revealed and validated by multiple data sets including field measured data, land use and land cover maps and findings from related research. This research provides basis in the avoidance of intensive field work and labor costs for visual interpretation of remote sensing image. The results show that the percentage of rangeland degradation is 32.86% in 1990 and 36.7% in 2004, indicating 3.84% increase in 15 years. The eastern part of the study area, comprising of Banma, Gadê, Henan, Jigzhi, Tongde and Zêkog had minimal degradation. The most severely degraded area is Qumarlêb, and its degraded rangeland accounted for 63.33% of the total area in 1990 and increased to 77.47% in 2004. The degradation at Madoi and Chindu is over 40%. It is found that the results on the spatio-temporal distribution of the rangeland degradation at TRHR are reasonable through various verifications. Thus, the novel approach is effective in monitoring rangeland degradation in an inaccessible region and harsh environment.